Hubungan Tingkat Pengetahuan Suami Tentang Pemberian Asi Eksklusif Terhadap Motivasi Ibu Dalam Menyusui Di Desa Ie Masen Kayee Adang Kecamatan Syiah Kuala Kota Banda Aceh - Tasnimin (STIKES Columbia Asia Medan, 2025)
Exclusive breastfeeding is a key strategy to improve child health and nutrition, yet its practice in Indonesia remains suboptimal. This study aimed to analyze the relationship between husbands’ knowledge about exclusive breastfeeding and mothers’ motivation to breastfeed in Ie Masen Kayee Adang Village, Syiah Kuala District, Banda Aceh City. Using a cross-sectional design, data were collected from 50 husbands whose wives were breastfeeding infants aged 0–12 months through questionnaires distributed directly and via Google Form. The instrument’s validity and reliability were tested and met the required standards. Data were analyzed using the Chi-Square test. The results showed that most husbands had a high level of knowledge (68%), and most mothers demonstrated high motivation to breastfeed (64%). The Chi-Square analysis indicated a significant relationship between husbands’ knowledge and mothers’ motivation (p = 0.039). These findings suggest that involving husbands as active partners in health promotion and breastfeeding education programs can increase maternal motivation and improve exclusive breastfeeding practices. This study highlights the importance of family-centered interventions to strengthen breastfeeding support and enhance maternal and child health outcomes.